IMPLEMENTATION OF ROLE PLAYING METHODS BASED ON SOCIAL ISSUES ARROUND STUDENTS TO INCREASE STUDENTS COOPERATION ON SOCIAL RELATIONSHIP IN SOCIAL STUDIES LEARNING (CLASSROOM ACTION RESEARCH AT CLASS VII-C MUHAMMADIYAH 6 JUNIOR HIGH SCHOOL BANDUNG) - Pertiwi, Suci Febriyanti (Universitas Pendidikan Indonesia, 2017)
Abstract-The purpose of this research is to increase cooperation among students through the role playing method on the students of class VIII-C Muhammadiyah 6 Junior High School Bandung academic year 2014/2015. This study uses a classroom action research approach. Subjects in this study were students in class VIII-C Muhammadiyah 6 Junior High School Bandung. of collecting data technique using Role Playing method and teacher achievement test. Action is done as much as 3 cycles, in one cycle done 2 times action. Data processing refers to qualitative procedures and changes in learning evaluation results before and after learning by using Role Playing method. The results showed: 1). The percentage of observation results of cooperation between friends on this 1st cycle has not been seen, because it is still within the range of